2012
DOI: 10.1258/ar.2012.120433
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic CT and MRI Findings of Intracranial Chondroma

Abstract: These characteristic CT and MR findings, combined with the location of the lesions and the history of a long duration of clinical symptoms, may prove helpful in differentiating intracranial chondromas from other more common tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…While calcification was evident in most of the reported falcine chondromas (60% to 90%), hyperostosis has been reported only in one falcine chondroma case (Table ). In consistent to other reports, MRI examination of the current case demonstrated mixed signal intensity on both T1WI and T2WI and revealed peripheral rim enhancement as well as central patchy enhancement with no dural tail. On the other hand, some authors reported no significant enhancement .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While calcification was evident in most of the reported falcine chondromas (60% to 90%), hyperostosis has been reported only in one falcine chondroma case (Table ). In consistent to other reports, MRI examination of the current case demonstrated mixed signal intensity on both T1WI and T2WI and revealed peripheral rim enhancement as well as central patchy enhancement with no dural tail. On the other hand, some authors reported no significant enhancement .…”
Section: Discussionsupporting
confidence: 92%
“…The mononucleated cells were enclosed within a chondroid matrix, with no signs of atypia or mitotic activities. Unlike in our case, other studies further performed immunohistochemistry and reported no immunoreactivity for Ki‐67 . Thus, it could be more useful for differentiating chondroma from malignant tumor such as chondrosarcoma or metastasis.…”
Section: Discussioncontrasting
confidence: 52%
“…They can be found as solitary lesions or as part of Ollier’s disease (multiple polysystemic enchondromatosis) or Maffuci’s syndrome 5 , 6 (multiple enchondromatosis associated with soft tissue angiomas). The publications regarding convexity chondromas are shown in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Chondromas have internal areas of calcification and more aggressive margins, unlike the circumscribed margins seen in this case. 11 A giant intraosseous aneurysm of the petrous segment of the internal carotid artery can result in an expansile mass; however, the internal carotid artery appeared to be distinct in this case, and linear areas of enhancement would not be expected within an aneurysm. The leading prospective imaging differential in this case was an expansile lesion with a myxoid matrix and fibrous contents, such as a chondromyxoid fibroma, fibromyxoma, or other related lesion.…”
Section: Case Reportmentioning
confidence: 56%